A Small Business as Investor - A Single Case Study of a Technology Adoption - Makkonen, Hannu (Piccola Impresa / Small Business, 2008)
In a fast changing environment a continual improvement in terms of identification, evaluation and implementation of new technological innovations is a critical factor for organizational productivity, competition and survival. The purpose of this paper is to scrutinize a technology adoption process of a small family business applying innovation adoption and diffusion frameworks. The empirical part of the study investigates an adoption process in which a small food processing company adopted a new aseptic packing machine. The internationalization of food processing industry combined with growing amount of global raw material sourcing is posing increasing challenges for companies, authorities and governments in terms of guaranteeing food safety. These circumstances offer an interesting and fruitful context in which to study a technology adoption process in a small business setting.